2016
DOI: 10.3402/jchimp.v6.33342
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis E presenting with clinical feature of autoimmune hepatitis

Abstract: A 32-year-old immigrant man presented with new onset jaundice. His past medical history was significant for type 2 diabetes mellitus, hypertension, and hyperlipidemia. His initial laboratory finding and liver biopsy were suggestive of autoimmune hepatitis (AIH). The plan was to start steroids pending negative results for viral serology, but it came back positive for hepatitis E virus. The patient's liver function test and clinical condition improved significantly on conservative management over a period of 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Since HEV is a zoonosis in industrialized countries and severe courses of autochthonous infections in immunosuppressed patients were reported, AIH patients should be counselled to avoid uncooked/undercooked food potentially infected with hepatitis E virus . Furthermore, case reports of acute HEV misdiagnosed as acute AIH have been published . Some of the patients described in these reports showed elevated IgG levels and positive autoantibody patterns strongly indicative for AIH as well as at least a “probable” diagnosis according to the established scoring systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since HEV is a zoonosis in industrialized countries and severe courses of autochthonous infections in immunosuppressed patients were reported, AIH patients should be counselled to avoid uncooked/undercooked food potentially infected with hepatitis E virus . Furthermore, case reports of acute HEV misdiagnosed as acute AIH have been published . Some of the patients described in these reports showed elevated IgG levels and positive autoantibody patterns strongly indicative for AIH as well as at least a “probable” diagnosis according to the established scoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, case reports of acute HEV misdiagnosed as acute AIH have been published. [37][38][39][40][41] Some of the patients described in these reports showed elevated IgG levels and positive autoantibody patterns strongly indicative for AIH as well as at least a "probable" diagnosis according to the established scoring systems. A study from…”
Section: Con Clus Ionsmentioning
confidence: 93%
“…Patel et al reported a case of acute hepatitis E mimicking AIH in a 32‐year‐old Bengali man, who recovered completely after supportive care. They suggested that steroid therapy should be postponed until HEV is ruled out 8 . Calisti et al 9 reported a case of acute hepatitis E in a patient with longstanding AIH under immunosuppressive therapy, which was mimicking a flare of AIH in a 44‐year‐old British woman.…”
Section: Discussionmentioning
confidence: 99%
“…HEV infection can cause asymptomatic, anicteric or icteric acute hepatitis as well as fulminant hepatitis, or acute‐on‐chronic liver failure. Moreover, this infection may not be readily recognized at times, as it may masquerade as DILI, AIH or with myriad of extrahepatic manifestations, such as neurological symptoms, acute pancreatitis, chronic renal disease and cryoglobulinaemic disease …”
Section: Discussionmentioning
confidence: 99%